Wanting is not (always) doing so: Some laboral problems of disabled people in the peruvian order - Bregaglio Lazarte, Renata Anahí (2016)
The present article has the objective of analysing the provisions that the peruvian State has been adopting for the implementation of the persons labour law with disabilities. In concrete, the article examines the provisions of the employment rate, the obligation to adopt reasonable settings and the bonification for the access to public employment. Additionally, it will develop some problems originated from this implementation and it will explain the remaining normative problems that still exist in the protection of other dimensions about labour colective law and people with disabilities.